2020
DOI: 10.1177/0020764020966020
|View full text |Cite
|
Sign up to set email alerts
|

Early indicators and risk factors associated with mental health problems during COVID-19 quarantine: Is there a relationship with the number of confirmed cases and deaths?

Abstract: Background: On March 20 2020, the Argentine Ministry of Health enforced a mandatory quarantine throughout the country in response to the COVID-19 pandemic. Aims: The object of this study is to determine the initial impact on mental health of Argentine population, by measuring the prevalence of anxiety, depression, insomnia, and self-perceived stress and by determining the associated risk factors, and to analyze that impact in relation to the number of confirmed cases and deaths. Method: A cross-sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Similar studies have been reported in studies conducted in the process of COVID-19. A study conducted in an Argentine population found that 62.4% of the participants showed symptoms of psychological distress ( Badellino et al, 2020 ). Xiong et al (2020) determined the rate of psychological distress in the general population to be from 34.43% to 38%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies have been reported in studies conducted in the process of COVID-19. A study conducted in an Argentine population found that 62.4% of the participants showed symptoms of psychological distress ( Badellino et al, 2020 ). Xiong et al (2020) determined the rate of psychological distress in the general population to be from 34.43% to 38%.…”
Section: Discussionmentioning
confidence: 99%
“…Islam et al ( Islam et al, 2020 ) determined being married to be a risk factor for general anxiety and panic levels. Badellino et al ( Badellino et al, 2020 ) identified living with family/partner to be a risk factor for psychological distress. In their study on anesthesia specialists in the COVID-19 pandemic period, Jain et al ( Jain et al, 2020 ) found being married to be a risk factor for anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Online surveys were conducted in Latin American countries like Argentina, Brazil, Colombia, and Mexico (14)(15)(16). These surveys covered mental health symptoms but only included one or just a few questions on alcohol consumption.…”
mentioning
confidence: 99%
“…A total of 36 unique samples from 33 studies (Badellino et al, 2020;Campos et al, 2020;Cénat et al, 2021;Chen et al, 2020a;Chen et al, 2020b;Civantos et al, 2020;Cortés-Álvarez et al, 2020;Dal'Bosco et al, 2020;De Boni et al, 2020;Fernández et al, 2020;Feter et al, 2021;Giardino et al, 2020;Goularte et al, 2021;Guiroy et al, 2020;Loret de Mola et al, in press;Malgor et al, 2020;Martinez et al, 2020;Medeiros et al, 2020;Monterrosa-Castro et al, 2020;Mora-Magaña et al, 2020;Paz et al, 2020;Puccinelli et al, 2021;Robles et al, 2020;Samaniego et al, 2020;Schuch et al, 2020;Scotta et al, 2021;Serafim et al, 2021;Torrente et al, 2021;Werneck et al, 2021;Jaime A. Yáñez et al, 2020; Jaime Stephen X Zhang et al, 2021;Stephen Xu Zhang et al, 2021) involving 101,772 participants from Latin America were included in this meta-analysis (Table 1). Some studies include multiple independent samples.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the random-effects model, the pooled prevalence of anxiety was 32% (95% CI: 27%-38%, I 2 = 99.8%) in the 29 studies (Figure 2A). A total of 27 samples from 24 studies (Badellino et al, 2020;Campos et al, 2020;Civantos et al, 2020;Cortés-Álvarez et al, 2020;Dal'Bosco et al, 2020;De Boni et al, 2020;Fernández et al, 2020;Feter et al, 2021;Giardino et al, 2020;Goularte et al, 2021;Guiroy et al, 2020;Loret de Mola et al, in press;Martinez et al, 2020;Medeiros et al, 2020;Mora-Magaña et al, 2020;Paz et al, 2020;Puccinelli et al, 2021;Robles et al, 2020;Samaniego et al, 2020;Schuch et al, 2020;Serafim et al, 2021;Torrente et al, 2021; Stephen X Zhang et al, in press) reported the prevalence of depression among 53,622 respondents. Among all the depression survey tools, the Patient Health Questionnaire (PHQ)-9 was the most frequently used (45.83%), followed by HADS (16.67%), DASS-21 (12.5%), and Beck Depression Inventory (BDI) (4.17%).…”
Section: Estimates Of Pooled Prevalence Of Psychological Morbidity Symptomsmentioning
confidence: 99%